Oxidative stabilization of high-PUFA biodiesel feedstocks using squalene: A multi-scale chemical and thermal analysis - V. Sharma; G. Griffiths; N. Collins; Abul K. Hossain; R. Sodré; D. Ganesh; R. Vinu; K. Anand (Bioresource Technology Reports, 2026)

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Preliminary insights into manta ray (Mobula alfredi and M. birostris) population demographics and distribution in South Africa - M. Carpenter; N. Cullain; R. Daly; G. Smith; M. Dicken; V. Dames; C. L. Griffiths; A. D. Marshall (Environmental Biology of Fishes, 2025)
Both the reef manta ray, Mobula alfredi and oceanic manta ray M. birostris , are repeatedly observed in South Africa, yet little is known about the distributions of either species. In this study, we collated citizen science observations since 2003 to reveal six areas in the KwaZulu-Natal (KZN) and Eastern Cape provinces, where manta rays have been sighted across multiple years. Using their unique ventral spot patterning, 184 individuals were photo-identified, comprising 139 M. alfredi and 45 M. birostris . Most of the photo-identified M. alfredi individuals were encountered in the iSimangaliso Wetland Park (IWP) in KZN (89%; n = 119) and for M. birostris , Aliwal Shoal (48%; n = 22). We identified 32 new transboundary records of 28 M. alfredi also photographed in the Inhambane Province, Mozambique, demonstrating connectivity, specifically to Závora ( n = 27). One M. alfredi individual traveled multiple times between the IWP and Závora, Mozambique, totaling 1305 km, and another individual traveled from the Pondoland MPA to the IWP in South Africa, a distance of over 600 km. Further, we extend the southern range for M. alfredi in Africa by over 500 km from Mdumbi Beach to Port Ngqura, Eastern Cape. These collective findings represent South Africa’s first in-water assessment of manta ray aggregations, showing the IWP in particular to be a critical habitat for M. alfredi . Further, the movements documented here suggest the M. alfredi population in southern Africa to be one of the most mobile globally. We hope the baseline data provided here will drive increased research and transboundary management for M. alfredi and M. birostris along the KZN and Eastern Cape coastlines.

Alkali-mediated Sr incorporation mechanism and binding capacity of alkali aluminosilicate hydrate in geopolymers - Daniel A. Geddes; Martin C. Stennett; Tom J. Wilkinson; Benjamin E. Griffith; John V. Hanna; John L. Provis; Brant Walkley (Journal of Hazardous Materials, 2025)

Mineralogic control on the calcium and magnesium stable isotopic compositions of modern microbial carbonates - Elizabeth M. Griffith; Matthew S. Fantle; Brittan V. Wogsland; Zijian Li; Majie Fan; David J. Wronkiewicz (Geochimica et Cosmochimica Acta, 2025)

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

Shear Strength of a Large Limestone Discontinuity: In Situ Pull Test and Prediction - Clarence Butcher; Olivier Buzzi; Anna Giacomini; Robert Bertuzzi; D. V. Griffiths; Stephen Fityus (Rock Mechanics and Rock Engineering, 2025)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Differential effects of microplastic exposure on leaf shredding rates of invasive and native amphipod crustaceans - Rose M. Griffith; James W. E. Dickey; Hannah M. Williams; Jack V. Johnson; Gary Hardiman; Jaimie T. A. Dick (Biological Invasions, 2024)
There is growing concern surrounding the pervasive impacts of microplastic pollution, but despite increasing interest in this area there remains limited understanding of its disruption to biological communities and the ecosystem services they provide. One such service is the breakdown of leaf litter in freshwaters by invertebrate shredders, such as Gammarus spp. , that directly and indirectly provides resources for many other species. This study investigates the effect of microplastic exposure on leaf consumption by two Gammarus species in Ireland, the native Gammarus duebeni celticus , and the invasive Gammarus pulex . Individuals were exposed to 40–48 μm polyethylene particles for 24 h at a range of concentrations (20–200,000 MP/L), with the amount of leaf consumption in that time frame recorded. Microplastics did not affect the feeding rate of either species at environmentally relevant concentrations, indicating that ecosystem services currently provided by our study species are sustainable. However, at higher microplastic concentrations the feeding rate of G. d. celticus was significantly reduced, whereas G. pulex remained unaffected, drawing attention to species-specific and native-invader differences in microplastic impacts. The results of our study further contribute to the observed pattern that invasive species, including various amphipod species, often display a higher tolerance to environmental stressors compared to their native counterparts. This research highlights the need for mitigation of ongoing and increasing microplastic pollution that could differentially influence key ecosystem services and functions.

Geotechnical laboratory testing of lunar simulants and the importance of standardization - V. Santiago Quinteros; Thomas Dylan Mikesell; Luke Griffiths; Alex X. Jerves (Icarus, 2024)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Renaming of genera Ebolavirus and Marburgvirus to Orthoebolavirus and Orthomarburgvirus, respectively, and introduction of binomial species names within family Filoviridae - Nadine Biedenkopf; Alexander Bukreyev; Kartik Chandran; Nicholas Di Paola; Pierre B. H. Formenty; Anthony Griffiths; Adam J. Hume; Elke Mühlberger; Sergey V. Netesov; Gustavo Palacios; Janusz T. Pawęska; Sophie Smither; et al. (Archives of Virology, 2023)

Resilient amphipods: Gammarid predatory behaviour is unaffected by microplastic exposure and deoxygenation - Rose M. Griffith; Ross N. Cuthbert; Jack V. Johnson; Gary Hardiman; Jaimie T.A. Dick (Science of The Total Environment, 2023)

Inhaled Adjunct Therapy with Second-Line Drug Candidates for Dose Reduction in Chemotherapeutic Regimens for Multi-drug-Resistant Tuberculosis - Sonia Verma; Nils-Jorgen K. Dal; Ashish Srivastava; Reena Bharti; D. V. Siva Reddy; Hasham Shafi Sofi; Trisha Roy; Khushboo Verma; Sunil K. Raman; Lubna Azmi; Lipika Ray; Madhav N. Mugale; et al. (AAPS PharmSciTech, 2023)

Whole Exome Sequencing of Hemiplegic Migraine Patients Shows an Increased Burden of Missense Variants in CACNA1H and CACNA1I Genes - Neven Maksemous; Aster V. E. Harder; Omar Ibrahim; Lisanne S. Vijfhuizen; Heidi Sutherland; Nadine Pelzer; Irene de Boer; Gisela M. Terwindt; Rodney A. Lea; Arn M. J. M. van den Maagdenberg; Lyn R. Griffiths (Molecular Neurobiology, 2023)
Hemiplegic migraine (HM) is a rare subtype of migraine with aura. Given that causal missense mutations in the voltage-gated calcium channel α1A subunit gene CACNA1A have been identified in a subset of HM patients, we investigated whether HM patients without a mutation have an increased burden of such variants in the “ CACNA1x gene family”. Whole exome sequencing data of an Australian cohort of unrelated HM patients ( n = 184), along with public data from gnomAD, as controls, was used to assess the burden of missense variants in CACNA1x genes. We performed both a variant and a subject burden test. We found a significant burden for the number of variants in CACNA1E ( p = 1.3 × 10 −4 ), CACNA1H ( p < 2.2 × 10 −16 ) and CACNA1I ( p < 2.2 × 10 −16 ). There was also a significant burden of subjects with missense variants in CACNA1E ( p = 6.2 × 10 −3 ), CACNA1H ( p < 2.2 × 10 −16 ) and CACNA1I ( p < 2.2 × 10 −16 ). Both the number of variants and number of subjects were replicated for CACNA1H ( p = 3.5 × 10 −8 ; p = 0.012) and CACNA1I ( p = 0.019, p = 0.044), respectively, in a Dutch clinical HM cohort ( n = 32), albeit that CACNA1I did not remain significant after multiple testing correction. Our data suggest that HM, in the absence of a single causal mutation, is a complex trait, in which an increased burden of missense variants in CACNA1H and CACNA1I may contribute to the risk of disease.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An Integrated Approach for Evaluation of Linear Cohesive Zone Model’s Performance in Fracturing of Rocks - Prasoon Garg; Bhardwaj Pandit; Ahmadreza Hedayat; D. V. Griffiths; Gandluri Lakshminarasimha Sivakumar Babu (Rock Mechanics and Rock Engineering, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Environmental DNA metabarcoding provides enhanced detection of the European eel Anguilla anguilla and fish community structure in pumped river catchments - Nathan P. Griffiths; Jonathan D. Bolland; Rosalind M. Wright; Leona A. Murphy; Robert K. Donnelly; Hayley V. Watson; Bernd Hänfling (Journal of Fish Biology, 2020)
The European eel Anguilla anguilla (eel hereafter) is critically endangered and has a catadromous life cycle, which means adult eels that live in pumped catchments must pass through pumps during their downstream spawning migration. Policy makers are currently lacking detailed site‐by‐site eel distribution information to estimate the overall impact of individual pumping stations on eel escapement, and as such lack the data to enable informed prioritisation of pumping station management and targeted mitigation. This study investigated whether environmental DNA (eDNA) metabarcoding can provide increased detection sensitivity for eel and fish community structure in highly regulated pumped catchments, when compared directly to current standard practice fish survey protocols (seine netting/electric fishing). Eels were detected in 14 of 17 sites (82.4%) using eDNA metabarcoding in contrast to 3 of 17 sites (17.6%) using traditional catch methods. In addition, when using eDNA monitoring, species richness was higher in 16 of 17 sites (94.1%), and site occupancy was greater than or equal to traditional methods for 23 of 26 of the fish species detected (88.5%). Although eDNA methods presented significantly higher average species richness and species site occupancy overall, eDNA and catch methods were positively correlated in terms of species richness and site occupancy. It was therefore found that eDNA metabarcoding was a high‐sensitivity method for detecting eels in pumped catchments while also increasing the detection of overall fish community structure compared to traditional catch methods. In addition, this study highlights how eDNA monitoring is especially suited to increase the detection of particular species, with traditional methods sufficient for others. This high sensitivity, coupled with the ability to sample multiple sites in a short time frame, suggests that eDNA metabarcoding workflows could be invaluable tools when prioritising pumping station management.

Geographic variation in life-history traits of the long-lived monacanthid Meuschenia scaber (Monacanthidae) - V. Visconti; E. D. L. Trip; M. H. Griffiths; Kendall D. Clements (Marine Biology, 2020)

Cluster analysis for the determination of the undrained strength tendency from SPT in mudflows and residual soils - Juan C. Viviescas; Juan P. Osorio; D. V. Griffiths (Bulletin of Engineering Geology and the Environment, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Vertical spatial correlation length based on standard penetration tests - Emir Ahmet Oguz; Nejan Huvaj; D. V. Griffiths (Marine Georesources & Geotechnology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Chronic graft-specific cell-mediated immune response toward candidate xenogeneic biomaterial - Katherine V. Gates; Leigh G. Griffiths (Immunologic Research, 2018)

Life‐history traits of the leatherjacket Meuschenia scaber , a long‐lived monacanthid - V. Visconti; E. D. L. Trip; M. H. Griffiths; K. D. Clements (Journal of Fish Biology, 2018)
The present study describes the age and growth of the leatherjacket Meuschenia scaber , a common Australasian monacanthid and valued by‐catch of the inshore bottom trawl fishery in New Zealand. Age was determined from the sagittal otoliths of 651 individuals collected between July 2014 and March 2016 in the Hauraki Gulf of New Zealand. Otolith sections revealed alternating opaque and translucent zones and edge‐type analysis demonstrated that these are deposited annually. Meuschenia scaber displayed rapid initial growth, with both males and females reaching maturity in 1–2 years and 50% of both sexes matured at 1·5 years. Maximum age differed substantially between the sexes, at 9·8 years for males and 17·1 years for females. Growth rate was similar between sexes, although males reached greater mass at age than females in the early part of the lifespan. The length–mass relationship differed significantly between the sexes, with males displaying negative allometric growth and females isometric growth. Female condition was highest in July, declined in August with the onset of spawning and showed a slight peak in January and February, immediately following the spawning season. This study substantially extends the maximum longevity recorded for monacanthids, although males had much shorter lifespans and higher mortality, than females.

On the efficient estimation of small failure probability in slopes - Jinsong Huang; Gordon Fenton; D. V. Griffiths; Dianqinq Li; Chuangbing Zhou (Landslides, 2017)

Society, marine ecosystems, innovation and change: current states of knowledge in South Africa - C L Moloney; V E Coyne; C L Griffiths; D Scott; M Sowman (African Journal of Marine Science, 2013)

Numerical Modeling of Pore Pressure Influence on Fracture Evolution in Brittle Heterogeneous Rocks - S. Y. Wang; S. W. Sloan; S. G. Fityus; D. V. Griffiths; C. A. Tang (Rock Mechanics and Rock Engineering, 2013)

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Interspecific and conspecific colony mergers in the dwarf honey bees Apis andreniformis and A. florea - S. Wongvilas; S. Deowanish; J. Lim; V. R. D. Xie; O. W. Griffith; B. P. Oldroyd (Insectes Sociaux, 2010)

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Synthesis and pharmacological characterization of [125I]MRS1898, a high-affinity, selective radioligand for the rat A3 adenosine receptor - Zhan-Guo Gao; Bao Teng; Haitao Wu; Bhalchandra V. Joshi; Gary L. Griffiths; Kenneth A. Jacobson (Purinergic Signalling, 2009)

Selenium Status of the Australian Population: Effect of Age, Gender and Cardiovascular Disease - Robyn Lymbury; Ujang Tinggi; Lyn Griffiths; Franklin Rosenfeldt; Anthony V. Perkins (Biological Trace Element Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A laboratory model of surface crust formation and disruption on lava flows through non-uniform channels - Katharine V. Cashman; Ross C. Kerr; Ross W. Griffiths (Bulletin of Volcanology, 2006)

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Characterisation of a barley (Hordeum vulgare L.) homologue of the Arabidopsis flowering time regulator GIGANTEA - R. P. Dunford; S. Griffiths; V. Christodoulou; D. A. Laurie (Theoretical and Applied Genetics, 2005)

Landscape Trends in Mid-Atlantic and Southeastern United States Ecoregions - Jerry A. Griffith; Stephen V. Stehman; Thomas R. Loveland (Environmental Management, 2003)

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Anchored simple-sequence repeats as primers to generate species-specific DNA markers in Lolium and Festuca grasses - I. Paäakinskiene; C. M. Griffiths; A. J. E. Bettany; V. Paplauskiene; M. W. Humphreys (Theoretical and Applied Genetics, 2000)

Identification of a new quantitative trait locus on Chromosome 7 controlling disease severity of collagen-induced arthritis in rats - Svetlana V. Dracheva; Elaine F. Remmers; Pércio S. Gulko; Yutaka Kawahito; Ryan E. Longman; Van R. Reese; Grant W. Cannon; Marie M. Griffiths; R. L. Wilder (Immunogenetics, 1999)

A genetic linkage map of rat chromosome 20 derived from five F 2 crosses - Y. Kawahito; Elaine F. Remmers; R. L. Wilder; Ryan E. Longman; Pércio S. Gulko; Jianping Wang; Stephen Chen; Lisa Chang; V. R. Reese; Svetlana Dracheva; Lynn Ge; Jean H. Hoffman; et al. (Immunogenetics, 1998)